Decision of the Supreme Court of Canada : the Lyon & the Wallrus - Alliance Quebec (AQ) (2002)

Everyone Is Invited to Picket Stores Where English is Banned - Alliance Quebec (AQ) (2002)

Alliance Quebec Supports Challenge to Bill 104 - Alliance Quebec (AQ) (2002)

Sophia and Dounia Badri Win Access to English School - Alliance Quebec (AQ) (2002)

Suggesting Change : The Situation of the English-speaking Minority of Quebec and Proposals for Change - Quebec Community Groups Network (QCGN) (2002)
Actions by the Government of Canada, such as the Speech from the Throne in January 2001, the nomination of Minister Stéphane Dion to coordinate the Federal Government's policy on official languages and chair the team of Ministers directly involved in Official Languages Policy and Program and his desire to develop an action plan to support the application of the Official Languages Act are encouraging. The demonstration of the political will of the Government to fulfill its obligation to ensure the full support of the development of vibrant and healthy Official-language minority communities throughout Canada is absolutely essential. It is, thus, incumbent on the Government that there is understanding and acceptance of the needs and realities of each linguistic minority community by both the majority populations and by those within the Canadian Government whose job is to develop and implement policy in support of the Francophone and Anglophone minority communities. The Official Languages Act must ensure the means and mechanisms for coordinated action and mobilization of the necessary resources to empower official minority language communities. As such, the action plan put forward by Minister Dion must be aimed at enabling the English-speaking minority in Quebec to build its own capacity, using solid facts and broad-based knowledge to be able to work with all governments to maintain and develop strong, vibrant English-speaking communities throughout Quebec.

The Twenty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2002)

Quebec Government Continues Harassment of Ethics - Alliance Quebec (AQ) (2002)

AQ Meets with the Standing and Senate Committee on Legal and Constitutional Affairs - Alliance Quebec (AQ) (2002)

Quebec is a Long Way from Linguistic Peace - Alliance Quebec (AQ) (2002)

Global Development Planning for the English-language Minority Communities of Quebec : Working Group Report Phase 1 : Preparation and Review - Quebec Community Groups Network (QCGN) (2002)
The Global Development Plan (GDP) Working Group has prepared the following report, which presents the conclusions and recommendations of the first phase of the GDP project entitled, Preparation and Review. This report is intended to guide the reader through the Working Group's reflection, discussion and analysis between December 2001 and March 2002.

Top Ten Red Flags in the Alan Greer Case - Alliance Quebec (AQ) (2002)

Canada Post Fires Whistle-Blower - Alliance Quebec (AQ) (2002)

Global Development Planning for the English-language Minority Communities of Quebec - Quebec Community Groups Network (QCGN) (2002)
The following discussion paper is a resource document created for the Global Development Plan (GDP) Working Group, which is based on highlights of various readings. The intention of this document is to generate discussion concerning the Quebec English-speaking community in terms of: How has the community evolved? Where are we now? Who are we?

Education Policy - Alliance Quebec (AQ) (2002)
The Education Policy of Alliance Quebec is based on certain fundam ental Guiding Principles. These principles are clearly articulated in certain international human rights obligations *(1) and domestic laws ** (2) to guarantee freedom, dignity and social justice for all in a democratic and free society.